Working conditions of subnational government workers in selected African countries (Cameroon, Ghana, Kenya, Morocco, Mozambique, and South Africa) - Zweli Julian Ndevu; Mary S. Mangai; Carlos Carrión-Crespo; David Kapya (International Labour Organization (ILO), 2024)
This report provides a comprehensive evaluation of the institutional and labour relations regimes in six African countries: Cameroon, Ghana, Kenya, Morocco, Mozambique, and South Africa with a special emphasis on promoting decent working conditions for Local and Regional Government (LRG) workers. It investigates the existing institutional and labour relations regimes by focusing specifically on their impacts on the working conditions of Local and Regional Government (LRG) workers and providing an analysis of each country's unique labour landscape shaped by historical, socio-economic, and political contexts. The report reveals that the effectiveness and scope of institutional and labour relations regimes vary significantly across these countries as they are influenced by historical, socio-economic, and political factors. Notwithstanding these differences, some shared challenges and promising practices emerge that provide useful insights for policymaking. South Africa's legal framework and institutionalized mechanisms for collective bargaining have led to significant advancements in working conditions for LRG workers. Nonetheless, gaps exist in implementation due to capacity constraints and resource limitations. Kenya and Mozambique have made some strides in establishing formal structures to negotiate wages and working conditions, although implementation remains uneven due to weak enforcement mechanisms. In Morocco, a recent shift towards a more participatory approach in local governance has begun to benefit LRG workers, but labour rights need to be fully embedded in this process to ensure widespread improvements in working conditions. Cameroon and Ghana, despite some legal provisions for collective bargaining, face substantial hurdles due to weak enforcement, low union density, and public sector restrictions on collective bargaining. In all six countries, issues such as low wages, poor employment conditions, and limited access to social protection remain prevalent. These challenges are often exacerbated for women LRG workers, who are under-represented in decision-making processes and face additional barriers related to gender discrimination. Despite these challenges, the report identifies several promising practices. These include capacity-building initiatives for labour unions, efforts to strengthen labour inspection systems, and innovative mechanisms to increase worker participation in decision-making processes. The report concludes that promoting decent working conditions for LRG workers in these countries requires a multi-pronged approach. This involves strengthening institutional and legal frameworks, enhancing the capacity of labour unions and other workers' representatives, improving enforcement mechanisms, promoting gender equality, and fostering a culture of social dialogue and worker participation. The findings of this report underline the need for continued efforts by governments, trade unions, employers, and other stakeholders to ensure that LRG workers have decent and dignified working conditions.
Keywords: 330; public sector; service sector